Association of health literacy and nutritional literacy with sun exposure in adults using structural equation modelling - Nasim SaeidiFard; Ali Asghar Haeri-Mehrizi; Zahra Akbarzadeh; Nasim Janbozorgi; Ali Montazeri; Mehdi Yaseri; Sakineh Shab-Bidar (BMC, 2022)
Abstract Background Inadequate health and nutritional literacy is a common problem among adults, associated with poor health outcomes. Therefore, this study aimed to investigate the relationship between health literacy and nutritional literacy to sun exposure behaviour. Methods We conducted a cross-sectional study on 261 adults (18-65 years) in Iran. Data was collected on knowledge, motivation, health literacy, nutritional literacy, and sun exposure behaviour using an interview-assisted questionnaire. Using the information-motivation-behavioural skills model and structural equation modeling, we tested whether health and nutritional literacy were associated with the relationships between knowledge of vitamin D, attitudes toward sun exposure, and sun exposure behaviour. Different models using structural equation modeling were performed to analyze the data. Results The finding showed that health literacy (β = 0.29, p < 0.001) and nutritional literacy (β = 0.14, p = 0.02) was directly associated with sunlight exposure. Indirect relationships also existed between knowledge and sunlight exposure through health literacy (β = 0.33, p < 0.001) and nutritional literacy (β = 0.22, p = 0.01). The model had good fit (x2/df = 1.422; RMSEA = 0.040; CFI = 0.851; NFI = 0.657). There was no significant relationship between health literacy and motivation (β = 0.11, p = 0.16), nutritional literacy and motivation (β = 0.06, p = 0.42) and motivation and sun exposure (β = 0.01, p = 0.91). Conclusions The findings showed that individuals with sufficient health literacy and nutritional literacy were more likely to have exposure to sunlight. Health and nutritional literacy should be considered when educating adults about vitamin D supplements and sunlight exposure.